Isolation and Characterization of Brucella spp., Low-Density Polyethylene (LDPE) Plastic Degrading Bacteria in Al-Ahsa Region, Saudi Arabia - Narjes J. Alamer; Munirah F. Aldayel; Ashraf Khalifa (Applied Sciences, 2023)
Plastic pollution is one of the most serious environmental issues, causing severe environmental damage. It is of vital importance to find an efficient and eco-friendly approach to biodegrading plastics. The aim of this study was to isolate and characterize different bacterial isolates from water samples in the Al-Ahsa region of Saudi Arabia. The ability to degrade low-density polyethylene (LDPE) plastic was evaluated using multiple approaches, including changes in the media pH values, weight loss, Fourier transform infrared (FTIR), and gas chromatography–mass spectrometry (GC–MS). The water samples were collected from plastic-contaminated sites in Al-Ahsa, and bacterial isolates were obtained using a mineral nutrient medium (MNM) enriched with LDPE as the only carbon and energy source. Two bacterial isolates (APCK5 and APCZ14) were obtained and they showed potential LDPE degradation, as evidenced by changes in media pH (from 7.0 ± 0.03 to 6.17 ± 0.05 and 6.22 ± 0.03), LDPE weight reduction (8.1 ± 0.63% and 18.85 ± 0.96%, respectively), and FTIR and GC–MS analyses. Based on 16S rRNA gene similarities, APCZ14 and APCK5 were determined to be most closely related to the genus Brucella. APCZ14 exhibited a 99.48% homology with Brucella cytisi, whereas APCK5 showed a 99.33% similarity level to Brucella tritici. In conclusion, both bacterial strains had high efficiency in plastic biodegradation and could be developed for wide use as an eco-friendly method to remove or reduce plastic pollutants from the environment.